Exploration of Multi-Component Vanadium and Titanium Pnictides Using Flux Growth and Conventional High-Temperature Methods - Ovchinnikov, Alexander; Bobev, Svilen (Frontiers in Chemistry, 2020)
The flux-growth method was successfully employed to synthesize millimeter-sized single crystals of the ternary barium vanadium pnictides Ba5V12As19+x (x ≈ 0.02) and Ba5V12Sb19+x (x ≈ 0.36), using molten Pb and Sb, respectively. Both compositions crystallize in space group P-43m and adopt a structure similar to those of the barium titanium pnictides Ba5Ti12Pn19+x (Pn = Sb, Bi), yet with a subtly different disorder, involving the pnictogen and barium atoms. Attempts to obtain an arsenide analog of Ba5Ti12Pn19+x using a Pb flux technique yielded binary arsenides. High-temperature treatment of the elements Ba, Ti, and As in Nb or Ta tubes resulted in side reactions with the crucible materials and produced two isostructural compositions Ba8Ti13–xMxAs21 (M = Nb, Ta; x ≈ 4), representing a new structure type. The latter structure displays fcc-type metal clusters comprised of statistically distributed Ti and M atoms (M = Nb, Ta) with multi-center and two-center bonding within the clusters, as suggested by our first-principle calculations.